Difficult Decisions in Endocrine Surgery An Evidence-Based Approach (Difficult Decisions in Surgery: An Evidence-Based Approach,, 2018)
This book provides a comprehensive overview of difficult decisions encountered within endocrine surgery. Brief uniformly formatted chapters are devoted to answering specific questions relevant to a range of topics across endocrine surgery based upon detailed analysis of available evidence.Topics covered include clinical decision analysis, decision making from the surgeon's and patient's perspective, using surgery as opposed to observation for papillary thyroid microcarcinoma, and the use of parathyroid cryopreservation. Difficult Decisions in Endocrine Surgery: An Evidence-Based Approach features a wealth of information on ideal approaches for making clinical decisions in selected clinical situations. It is an important and timely resource for all endocrine surgical trainees, fellows, practitioners, educators, and healthcare providers involved in the management of these patients. .